Phytochemical Screening, Isolation and Characterisation of Phytoconstituents of Lagerstroemia lanceolata - Joshi, Namita; Joshi, Neha; Joshi, Himanshu (Asian Journal of Chemistry, 2026)
The present study focuses on the phytochemical screening, isolation and characterisation of phytoconstituents from Lagerstroemia lanceolata, a medicinally significant species known for its diverse therapeutic applications. Preliminary phytochemical evaluation of the methanolic extract confirmed the presence of major secondary metabolites, prompting further purification. Thin layer chromatography (TLC) was employed to optimize the solvent system for separation, where the mobile phase toluene:ethyl acetate (7.5:2.5) provided superior resolution of phytoconstituents. Based on the TLC analysis, column chromatography resulted in the isolation of three pentacyclic triterpenoids, namely oleanolic acid, ursolic acid and corosolic acid. Structural elucidation and confirmation of purity were achieved using a combination of spectroscopic techniques, including IR, 1H NMR, 13C NMR and LC-MS.